TNIK regulation of interferon signaling and endothelial cell response to virus infection - Chau, Khanh M.; Dominic, Abishai; Davis, Eleanor L.; Kotla, Sivareddy; Berrios, Estefani Turcios; Fahim, Arsany; Arunesh, Ashwin; Li, Shengyu; Zhao, Dongyu; Chen, Kaifu; Davis, Alan R.; Nguyen, Minh T. H.; et al. (Frontiers in Cardiovascular Medicine, 2024)
Background: Traf2 and Nck-interacting kinase (TNIK) is known for its regulatory role in various processes within cancer cells. However, its role within endothelial cells (ECs) has remained relatively unexplored. Methods: Leveraging RNA-seq data and Ingenuity Pathway Analysis (IPA), we probed the potential impact of TNIK depletion on ECs. Results: Examination of RNA-seq data uncovered more than 450 Differentially Expressed Genes (DEGs) in TNIK-depleted ECs, displaying a fold change exceeding 2 with a false discovery rate (FDR) below 0.05. IPA analysis unveiled that TNIK depletion leads to the inhibition of the interferon (IFN) pathway (-log (p-value) >11), downregulation of IFN-related genes, and inhibition of Hypercytokinemia/Hyperchemokinemia (-log (p-value) >8). The validation process encompassed qRT-PCR to evaluate mRNA expression of crucial IFN-related genes, immunoblotting to gauge STAT1 and STAT2 protein levels, and ELISA for the quantification of IFN and cytokine secretion in siTNIK-depleted ECs. These assessments consistently revealed substantial reductions upon TNIK depletion. When transducing HUVECs with replication incompetent E1-E4 deleted adenovirus expressing green fluorescent protein (Ad-GFP), it was demonstrated that TNIK depletion did not affect the uptake of Ad-GFP. Nonetheless, TNIK depletion induced cytopathic effects (CPE) in ECs transduced with wild-type human adenovirus serotype 5 (Ad-WT). Summary: Our findings suggest that TNIK plays a crucial role in regulating the EC response to virus infections through modulation of the IFN pathway.